ETUDE DES PROPRIETES DES COUCHES MINCES DU COMPOSITE NICKEL-ALUMINE ELABOREES PAR ELECTRODEPOSITION - Soumaia REGHAISSIA (My University, 2022)
In this work, the objective is to give a study on the effect of electroplating parameters on the mechanical properties and electrochemical characteristics: thin layers of Ni-Al2O3 composite electrodeposited on a copper substrate previously treated from the watts bath. The centered composite design was used to study the effects of operational parameters on the microhardness and roughness of Ni-Al2O3 composite deposits. The results obtained showed that the resulting prediction model is significant, so there is a correlation between the factors studied and the response function, statistical analysis show that the effect of the current density contribution is highest for both response functions. Also we have the optimal values of the operating parameters corresponding to a maximum microdurty and a minimum roughness of the electrolytic deposits. The cyclic voltammetry kinetic study explained the nucleation and growth mechanism, and confirmed that the electrochemical reaction of nickel species is controlled by diffusion. We also found that sodium dodecyl sulphate and alumina slow down the kinetics of nickel electroplating. Thanks to their inhibitory effect, alumina reduces the size of the deposited nickel molecules, making the dance surface more homogeneous. -------------------------------------------------------------------------------------- هذا العمل يهدف الى إجراء دراسة حول تأثير عوامل الطلاء الكهربائي على الخصائص الميكانيكية والخصائص الكهروكيميائية: يتم تشكيل طبقات رقيقة من المركب Ni-Al2O3 على ركيزة نحاسية عولجت سابقًا من حمام watts . تم استخدام التصميم المركب المركز لدراسة تأثيرات المعلمات التشغيلية على الصلابة الدقيقة وخشونة السطح للمركب المترسب, Ni-Al2O3 . أظهرت النتائج التي تم الحصول عليها أن نموذج التنبؤ الناتج مهم، لذلك هناك علاقة بين العوامل التي تمت دراستها ووظيفة الاستجابة، ويظهر التحليل الإحصائي أن تأثير مساهمة الكثافة الحالية هو الأعلى لكلا وظيفتي الاستجابة. لدينا أيضًا القيم المثلى لمعلمات التشغيل التي تتوافق مع أقصى قدر من الجراحة الدقيقة والحد الأدنى من خشونة الرواسب الكهربائية . شرحت الدراسة الحركية للفولتامتري الدوري آلية التنوية والنمو، وأكدت أن التفاعل الكهروكيميائي لأنواع النيكل يتم التحكم فيه عن طريق الانتشار. وجدنا أيضًا أن كبريتات دوديسيل الصوديوم والألومينا تبطئ حركية الطلاء الكهربائي بالنيكل. بفضل تأثيرها المثبط، تقلل الألومينا من حجم جزيئات النيكل المترسبة، مما يجعل سطح الرقص أكثر تجانسًا. ----------------------------------------------------------------------------------- La présente étude est basée sur l’élaboration et l'évaluation de l'effet des paramètres opératoires sur les propriétés mécaniques et électrochimiques des couches minces de composite Ni-Al2O3 électrodéposés sur un substrat de cuivre. Le plan composite centré a été utilisée pour étudier les effets des paramètres opérationnels à savoir ; la température, la densité de courant, la concentration du dodécyl sulfate de sodium et la concentration de l’alumine sur la microdurté et la rugosité des dépôts composites Ni-Al2O3. Les résultats obtenus ont montré que le modèle de prédiction obtenu est significatif, donc il y a une corrélation entre les facteurs étudiés et les fonction réponse, l’analyse statistiques montrent que l’effet de la contribution de la densité de courant est la plus élevé pour les deux fonctions réponse. Également nous avons les valeurs optimales des paramètres opératoires correspond à une microdurté maximal et une rugosité minimale des dépôt électrolytiques. L’étude cinétique par voltampérométrie cyclique a expliqué le mécanisme de nucléation et de croissance, et a confirmé que la réaction électrochimique des espèces de nickel est contrôlée par diffusion. Également nous avons trouvé que le dodécyl sulfate de sodium et l’alumine ralentissent la cinétique de l’électrodéposition du nickel. Grâce à leur effet inhibiteur, l’alumine réduit la taille des molécules de nickel déposées, ce qui rend la surface dance et plus homogène.